2016
DOI: 10.1530/joe-15-0533
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and sarcopenia: mechanistic links between common co-morbidities

Abstract: Insulin resistance (IR) in skeletal muscle is a key defect mediating the link between obesity and type 2 diabetes, a disease that typically affects people in later life. Sarcopenia (age-related loss of muscle mass and quality) is a risk factor for a number of frailty-related conditions that occur in the elderly. In addition, a syndrome of 'sarcopenic obesity' (SO) is now increasingly recognised, which is common in older people and is applied to individuals that simultaneously show obesity, IR and sarcopenia. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
320
4
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 427 publications
(333 citation statements)
references
References 154 publications
1
320
4
8
Order By: Relevance
“…However, muscle of older individuals with type 2 diabetes [29] metabolic syndrome [30] demonstrated a significant low proportion of type I fibers that is positively associated with the severity of insulin resistance. Thus, the loss of muscle mass and the alterations of myofiber type proportion due to insulin resistance could potentially affect whole body glucose homeostasis [31]. Age-related hormone changes, for example, the decline of anabolic hormone testosterone leads to the loss of both muscle mass and strength [32].…”
Section: Aging Promotes Sarcopenia and Frailtymentioning
confidence: 99%
See 2 more Smart Citations
“…However, muscle of older individuals with type 2 diabetes [29] metabolic syndrome [30] demonstrated a significant low proportion of type I fibers that is positively associated with the severity of insulin resistance. Thus, the loss of muscle mass and the alterations of myofiber type proportion due to insulin resistance could potentially affect whole body glucose homeostasis [31]. Age-related hormone changes, for example, the decline of anabolic hormone testosterone leads to the loss of both muscle mass and strength [32].…”
Section: Aging Promotes Sarcopenia and Frailtymentioning
confidence: 99%
“…Muscle growth promoters through their receptors phosphorylate SMAD 1/5/8 decrease the inhibition of Alt/mTOR signal and maintain muscle mass and strength. Insulin resistance due to aging, obesity, and diabetes results in the suppression of insulin/insulin-like growth factor-1/phosphatidyl Inositol 3-kinase/protein kinase B (IGF 1/PI3K/AKT)/mTOR, and muscle hypotrophy and dysfunction of metabolism; the less activated Alk fails to block the nuclear translocation of Foxo 3 to enhance the expression of autophagy-related genes and the consequent protein degradation [31,52].…”
Section: The Maintenance Of Muscle Mass and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…

Insulin signaling and energy metabolism (ISEM: denoted by insulin, C‐peptide, leptin). Based on present evidence, it remains unclear whether increased insulin resistance or reduced endogenous insulin secretion (or both) is underlying mechanisms in sarcopenia and frailty (Cleasby et al, 2016; Tanaka, Kanazawa, & Sugimoto, 2015). Our result shows that low fasting plasma insulin and C‐peptide (a better measure of portal insulin secretion) levels are associated with low muscle mass and function and suggests that in this Asian group, endogenous reduction of insulin level and dysregulated insulin signaling activity in older individuals (with and without diabetes) diminish the anabolic capacity of insulin to alleviate muscle protein breakdown in skeletal muscles.

…”
Section: Introductionmentioning
confidence: 98%
“…Circulating insulin (Barzilay et al, 2007; Cleasby, Jamieson, & Atherton, 2016), testosterone (Auyeung et al, 2011), insulin‐like growth factor‐1 (IGF‐1; Gielen et al, 2015), and dehydroepiandrosterone sulfate (DHEAS; Tajar et al (2011)) have been interrogated in a majority of studies mostly in isolation and with conflicting results. In contrast, several studies, such as the InCHIANTI Study, the WHAS I and II, and the MSSA (Fried et al, 2009; Gruenewald, Seeman, Karlamangla, & Sarkisian, 2009; Maggio et al, 2010), have found that an increased number of multiple hormonal biomarker abnormalities strongly predict physical frailty when individual biomarker abnormalities did not.…”
Section: Introductionmentioning
confidence: 99%